2015
DOI: 10.3109/19390211.2015.1008616
|View full text |Cite
|
Sign up to set email alerts
|

Complementary Cholesterol-Lowering Response of a Phytosterol/α-Lipoic Acid Combination in Obese Zucker Rats

Abstract: To investigate the cholesterol-lowering effectiveness of a phytosterol/α-lipoic acid (PS/αLA) therapy, thirty-two male Zucker rats were randomly assigned to 1 of 4 diets for 30 days: (i) high fat diet (HF, 40% energy from fat); (ii) HF diet supplemented with 3% phytosterols; (iii) HF diet supplemented with 0.25% αLA; or (iv) HF diet supplemented with PS (3%) and αLA (0.25%, PS/αLA). Compared with the HF diet, combination PS/αLA proved more effective in reducing non-HDL cholesterol (−55%) than either the PS (−2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 48 publications
(58 reference statements)
0
11
0
3
Order By: Relevance
“…This gene expression pattern may well reflect an effort to restore cholesterol lipid balance as cholesterol is critical for early development [ 43 ]. Although there are no other maternal PS supplementation studies with which to compare our gene expression data, previous PS supplementation studies in adult animals have reported variable expression of NCP1L1 [ 44 47 ] and a more consistent increase in HMG-CoAr expression [ 48 , 49 ] and cholesterol synthesis [ 50 52 ].…”
Section: Main Textmentioning
confidence: 99%
“…This gene expression pattern may well reflect an effort to restore cholesterol lipid balance as cholesterol is critical for early development [ 43 ]. Although there are no other maternal PS supplementation studies with which to compare our gene expression data, previous PS supplementation studies in adult animals have reported variable expression of NCP1L1 [ 44 47 ] and a more consistent increase in HMG-CoAr expression [ 48 , 49 ] and cholesterol synthesis [ 50 52 ].…”
Section: Main Textmentioning
confidence: 99%
“…Many animal and human studies report that LA supplementation can result in reduced cholesterol levels [ 89 , 90 ]. LA may also prevent LDL oxidation by reducing the concentrations of LDL-C, Ox-LDL, serum TC, and lipoprotein (a) [Lp(a)], as well as other oxidative biomarkers [ 85 ].…”
Section: Protective Effect Of Lipoic Acid (La) On Cardiovascular Dmentioning
confidence: 99%
“…; Rideout et al. ). ALA has also been shown to increase high‐density lipoprotein (HDL) cholesterol levels in high‐fat diet‐fed rats (Miao et al.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, ALA has been shown to protect arterial lesion formation in vitro (Lee et al 2012). Conversely, no changes in serum total cholesterol and/or triglyceride levels were observed in streptozotocin-induced diabetic rats (Salama 2011) and in HFD-fed obese Zucker rats (Carrier et al 2014;Rideout et al 2016). ALA has also been shown to increase high-density lipoprotein (HDL) cholesterol levels in high-fat diet-fed rats (Miao et al 2013).…”
Section: Introductionmentioning
confidence: 99%